Penanggulangan Krisis Kesehatan di Indonesia Tahun 2016 - Masdalina Pane; Ina Agustina Isturini; Mugi Wahidin (Media Penelitian dan Pengembangan Kesehatan, 2018)
AbstractHealth crisis is an event/series of events that threaten the health of individuals or communities caused by disasters and / or potentially disasters. Researchs on health crisis as scientific source in disaster policy making in Indonesia is still very limited. The description of health crises events of including victims, displacement and damage to health facilities and support for health crisis response in the form of emergency response along with the initial recovery by the Ministry of Health in 2016 were the aims of this study. This study is a qualitative study, using literature review method, reference / electronic information tracking such as through Health Crisis Management Information System, National Disaster Management Agency (BNPB) website, Regional Disaster Management Agency (BPBD), Social Service, Regional Government Police and other related agencies. Secondary data from related units/agencies and the main Ministry of Health units are obtained through focus group discussions (FGDs). The frequency of health crisis events due to the disaster in 2016 was 661 incidents dominated by natural disasters as many as 400 events (60%), while the frequency of non-natural disasters was 237 events (36%) and social disasters 24 events (4%). Most of the health crisis incidents due to the 2016 disaster (97%) were the remaining hydrometeorological disasters, 3% of the most non-natural disasters were outbreaks of food poisoning, transportation accidents, fire, technology failure, industrial accidents and outbreaks of disease. The ratio of refugees due to natural disaster is 693 per event, while social disasters are 225 per incident The ratio of deaths from non-natural disasters is 1.5 times higher than natural disaster. Poisoning has the highest victim ratio of 20 per incident of poisoning. Health facility damage caused by disaster 174 units. The greatest health impacts arising from the health crisis in 2016 was. dominated by natural disasters in the forms of floods, landslides and earthquake disasters. Effective emergency response efforts must involve as many sub-clusters as possible that have special expertise to overcome the impact on disasters. AbstrakKrisis kesehatan merupakan peristiwa/rangkaian peristiwa yang mengancam kesehatan individu atau masyarakat yang disebabkan oleh bencana dan/atau berpotensi bencana. Penelitian tentang krisis kesehatan sebagai sumber ilmiah dalam pengambilan kebijakan kebencanaan di Indonesia masih sangat terbatas. Deskripsi kejadian krisis kesehatan meliputi korban, pengungsian dan kerusakan fasilitas kesehatan serta penanggulangan krisis kesehatan dalam bentuk tanggap darurat beserta pemulihan awal yang dilakukan Kementerian Kesehatan pada tahun 2016 menjadi tujuan dari kajian ini. Kajian ini merupakan kajian kualitatif, menggunakan metode literature review, penelusuran referensi/informasi elektronik seperti melalui Sistem Informasi Penanggulangan Krisis Kesehatan, website Badan Nasional Penanggulangan Bencana (BNPB), Badan Penanggungalan Bencana Daerah (BPBD), Dinas Sosial, Kepolisian Pemerintah Daerah dan instansi terkait lainnya. Data primer dari unit/instansi terkait dan unit utama kementerian kesehatan didapatkan melalui focus group discussion (FGD). Frekuensi kejadian krisis kesehatan akibat bencana pada tahun 2016 sejumlah 661 kejadian, juga didominasi oleh bencana alam sebanyak 400 kejadian (60%), sementara frekuensi bencana non alam 237 kejadian (36%) dan bencana sosial 24 kejadian (4%). Sebagian besar kejadian krisis kesehatan akibat bencana tahun 2016 (97%) merupakan kejadian bencana hidrometeorologi sisanya 3% bencana non alam terbanyak adalah KLB Keracunan makanan, kecelakaan transportasi, kebakaran, gagal teknologi, kecelakaan industri dan KLB Penyakit. Rasio pengungsi akibat bencana alam sebesar 693 per kejadian, sedangkan bencana sosial 225 per kejadian. Rasio kematian akibat bencana non alam 1.5 kali lebih tinggi daripada bencana alam. Keracunan mempunya rasio korban tertinggi sebesar 20 per kejadian keracunan. Kerusakan fasilitas kesehatan akibat bencana 174 unit. Dampak kesehatan terbesar yang timbul akibat kejadian krisis kesehatan di tahun 2016, didominasi oleh bencana alam berupa bencana banjir, banjir bandang dan tanah longsor serta bencana gempa bumi.